Music of the first nations : tradition and innovation in native North America - Browner, Tara, 1960- (Urbana : University of Illinois Press, 2009)
This unique anthology presents a wide variety of approaches to an ethnomusicology of Inuit and Native North American musical expression. Contributors include Native and non-Native scholars who provide erudite and illuminating perspectives on aboriginal culture, incorporating both traditional practices and contemporary musical influences.
Iglulik Inuit drum-dance songs / Paula Conlon -- Musical expressions of the Dene : dogrib love and land songs / Lucy Lafferty and Elaine Keillor -- The story of dirty face : power and song in western Washington Coast Salish myth narratives / Laurel Sercombe -- Drum, songs, vibrations : conversations with a Passamaquoddy traditional singer / Franziska von Rosen (introduction by Tara Browner) -- Identity, retention, and survival : contexts for the performance of native Choctaw music / David E. Draper -- "This is our dance" : the fire dance of the Fort Sill Chiricahua Warm Springs Apache / T. Christopher Aplin -- The creative power and style of ghost dance songs / Judith Vander -- An acoustic geography of intertribal pow-wow songs / Tara Browner -- Singing Indian country / David W. Samuels.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Indians of North America -- Music -- History and criticism; Indian dance -- North America; Danses des Peuples autochtones -- Amérique du Nord; MUSIC -- Ethnic; MUSIC -- Genres & Styles -- Folk & Traditional; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies; Ethnomusicology; Indian dance; Indians of North America -- Music; North America; United States; Folk, Ethnic & World music; Indigenous peoples; Criticism, interpretation, etc; History